Analisis Risiko Kredit Bermasalah terhadap Return On Equity (ROE): Studi Kasus Pada Unit Simpan Pinjam Koperasi Serba Usaha Budidaya - Wahyudin, Wahyudin; Purnamasari, Ririn (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This research aims to find out how risk management is implemented by the KSU Cultivation Savings and Loans Unit to minimize the increasing loan risk, as well as to prove that there is a relationship between Loan Risk and Return On Equity (ROE) at the KSU Cultivating Savings and Loans Unit. The types of data used in research are primary data and secondary data. Data collection techniques include observation, interviews and literature study. The KSU Budidaya Savings and Loans Unit has implemented a risk management process including identifying risks, measuring risks and managing risks. And also in the strategy for handling credit risk in the Savings and Loans Unit, the cooperative has implemented the 5C principle (Character, Capacity, Capital, Condition and Collateral) in providing loans. From the results of the relationship between Loan Risk (X) and Return On Equity (ROE) (Y), it is known that r = 0.41, which means that credit risk and ROE have a fairly strong or fairly close relationship. Thus, it can be said that if loan risk increases, the ROE level will decrease, and conversely, if loan risk decreases, this will be followed by an increase in the ROE level.